Neurologic Complications of Enterovirus 71 Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The neurologic complications associated with the 1998 Taiwan enterovirus 71 epidemic are reported from National Cheng Kung University, Tainan; Chang Gung Children's Hospital, Kaohsiung; and National Defense Medical Center, Taipei, Taiwan.